Diabetes mellitus and pregnancy - Fathi I Abourawi (Libyan Journal of Medicine, 2006)
Diabetes mellitus is the most common medical complication of pregnancy and it carries a significant risk to the foetus and the mother. Congenital malformations and perinatal morbidity remain common compared with the offspring of non diabetic pregnancies. Diabetic mothers are at risk of progression of micro-vascular diabetic complications as well as early pregnancy loss, pre-eclampsia, polyhydramnios and premature labour. Glycaemic control before and during pregnancy is critical and the benefit may result in a viable, healthy offspring. Gestational diabetes mellitus (GDM) which manifests for the first time during pregnancy is common and on the increase, its proper management will reduce the risk of neonatal macrosomia and hypoglycaemia. Post-partum evaluation of glucose tolerance and appropriate counselling in women with GDM may help decrease the high risk of subsequent type 2 diabetes in the long-term. The article will briefly review the changes in the carbohydrate metabolism that characterise normal pregnancy and will focus on a practical approach to the care of patients with pre-existing diabetes as well as GDM.